2001
DOI: 10.1080/000164801300006245
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Variations of the Inner Ear

Abstract: Vascular anomalies of the inner ear have been documented in only a few isolated case reports. The goal of our study was to describe, qualify and quantify vascular variations of the inner ear in 122 temporal bones from 64 pediatric subjects aged between 0 and 10 years. The average age was 11.6 months. Horizontal sections of the temporal bone, examined by light microscopy, revealed vessels coursing freely through the perilymphatic space of the cochlea, especially in the apical turn. Other findings included abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In the crude model, pure-tone audiometry thresholds and speech test results were significantly worse in participants with hypertension than in those without hypertension. These findings are consistent with the findings from previous studies showing that individuals with hypertension were at a high risk of HL (8,(24)(25)(26)(27)(28). However, except those at the frequencies of 6 and 8 kHz in the left ear, the hearing thresholds did not show significant differences between individuals with and without hypertension after adjusting for age.…”
Section: ' Discussionsupporting
confidence: 91%
“…In the crude model, pure-tone audiometry thresholds and speech test results were significantly worse in participants with hypertension than in those without hypertension. These findings are consistent with the findings from previous studies showing that individuals with hypertension were at a high risk of HL (8,(24)(25)(26)(27)(28). However, except those at the frequencies of 6 and 8 kHz in the left ear, the hearing thresholds did not show significant differences between individuals with and without hypertension after adjusting for age.…”
Section: ' Discussionsupporting
confidence: 91%
“…Second, increased blood viscosity could induce tissue hypoxia by decreasing capillary blood flow and oxygen transport. Third, arterial hypertension could cause progressive or sudden hearing loss by inducing ionic changes in cell potentials [16] [18] . In this study of subjects who underwent health screening examinations, the prevalence of hearing loss was significantly higher in those with than without hypertension (10.9% vs. 6.6%), although multivariate analysis showed that hypertension was not an independent predictor of hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension causes hemorrhage in the inner ear, leading to reductions in capillary blood flow and oxygen supply and resulting in progressive or sudden sensorineural hearing loss [ 29 ]. Hypertension also reduces blood flow by reducing the inner diameter of blood vessels in the inner ear through atherosclerosis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%